Goldman and his critics - McLaughlin, Brian P.; Kornblith, Hilary (Wiley, 2016)
Goldman and His Critics presents a series of original essays contributed by influential philosophers who critically examine Alvin Goldman's work, followed by Goldman's responses to each essay. -Critiques Alvin Goldman's groundbreaking theories, writings, and ideas on a range of philosophical topics -Features contributions from some of the most important and influential contemporary philosophers -Covers Goldman's views on epistemology-both individual and social-in addition to cognitive science and metaphysics -Pays special attention to Goldman's writings on philosophy of mind, including the evolution of his thoughts on Simulation-Theory (ST)
Includes bibliographical references and index
Keywords: Goldman, Alvin I. / 1938-; Goldman, Alvin I. -- 1938-; PHILOSOPHY / History & Surveys / Modern; Kritik; Aufsatzsammlung